Synthesis and Evaluation of Voltage‐Gated Sodium Channel Blocking Pyrroline Derivatives Endowed with Both Antiarrhythmic and Antioxidant Activities. (28th October 2020) - Carocci, Alessia; Roselli, Mariagrazia; Budriesi, Roberta; Micucci, Matteo; Desaphy, Jean‐François; Altamura, Concetta; Cavalluzzi, Maria Maddalena; Toma, Maddalena; Passeri, Giovanna Ilaria; Milani, Gualtiero; Lovece, Angelo; Catalano, Alessia; et al.
Abstract: Under the hypothesis that cardioprotective agents might benefit from synergism between antiarrhythmic activity and antioxidant properties, a small series of mexiletine analogues were coupled with the 2, 2, 5, 5‐tetramethylpyrroline moiety, known for its antioxidant effect, in order to obtain dual‐acting drugs potentially useful in the protection of the heart against post‐ischemic reperfusion injury. The pyrroline derivatives reported herein were found to be more potent as antiarrhythmic agents than mexiletine and displayed antioxidant activity. The most interesting tetramethylpyrroline congener, a tert ‐butyl‐substituted analogue, was at least 100 times more active as an antiarrhythmic than mexiletine. Abstract : Compounds with heart : Investigations into the antiarrhythmic and antioxidant potential of a series of pyrroline derivatives identified a potent antiarrhythmic agent (2 b ), more active than the parent compound mexiletine. Because it also displays antioxidant activity, it is a good candidate for the development of dual‐acting drugs potentially useful in protecting the heart against post‐ischemic reperfusion injury.